UPAYA UPT P2TK JAWA TIMUR DALAM PELINDUNGAN HUMAN SECURITY POST-MORTEM BAGI PMI NON-PROSEDURAL: STUDI KASUS PENANGANAN JENAZAH PMI DI JEPANG TAHUN 2024: EFFORTS BY THE EAST JAVA UPT P2TK IN POST-MORTEM HUMAN SECURITY PROTECTION FOR NON-PROCEDURAL PMI: CASE STUDY ON THE HANDLING OF PMI DEATHS IN JAPAN IN 2024 - Sabil, Rafil Ibnu; Moh. Fathoni Hakim (Journal of Administration and International Development, 2025)
This research explores the efforts of UPT P2TK East Java in providing Human Security Post-Mortem protection for undocumented Indonesian Migrant Workers (PMI) who died in Japan in 2024. The rising number of non-procedural PMI working illegally abroad presents significant challenges, particularly when they pass away in destination countries—raising complex issues of post-mortem rights and dignity. This study focuses on a case involving the repatriation of a deceased undocumented PMI from East Java who had overstayed in Japan, analyzing how UPT P2TK facilitated the return of the body, managed administrative procedures, and supported the victim’s family. Using a descriptive qualitative approach, data was collected through document analysis, interviews, and literature review. The concept of Human Security Post-Mortem serves as the analytical framework to evaluate the state’s role, through UPT P2TK, in ensuring the protection of human dignity after death, especially in the context of irregular migration. The findings indicate that UPT P2TK played a significant role in body identification, document processing, and inter-agency coordination. However, challenges remain, particularly regarding the absence of specific regulations and limited emergency funding. This study underlines the urgent need to develop a more structured and responsive post-mortem protection system to fully uphold human security—extending not only during life but also beyond death. Keywords: UPT P2TK, Human Security, Post-Mortem, Indonesian Migrant Workers, Non-Procedural, Corpses